2016
DOI: 10.1177/0972262916628946
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Consumer Search and Evaluation Behaviour: Effect of Brand Name and Price Perceptions

Abstract: Past researchers extended the conceptualized model of perceived value to include the effects of multiple extrinsic cues used as indicators of quality. The need for replication as well as extending the research findings has, however, been expressed unequivocally by the researchers as it remains to be seen if the existing relationships would hold for consumers hailing from emerging nations. The present study extends the theoretical and empirical evidences regarding the structural relationships of consumers' perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(172 reference statements)
1
5
0
Order By: Relevance
“…However, Chu (Chu, 2018) found that price did not significantly affect the intention to purchase green products. A similar results were found by Sharma and Garg (2016) and Alex and Mathew (2018).…”
Section: Pricesupporting
confidence: 89%
“…However, Chu (Chu, 2018) found that price did not significantly affect the intention to purchase green products. A similar results were found by Sharma and Garg (2016) and Alex and Mathew (2018).…”
Section: Pricesupporting
confidence: 89%
“…Purchase intention refers to the tendency of a shopper to buy the brand (Diallo and Seck, 2018 ). It is also a key element for the long-term success of relationships (Sharma and Garg, 2016 ). With a well-established brand name, buyers generally have to spend very less time perceiving the quality of the product (Randhawa et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, previous studies do not also completely describe the impact of the packaging cues on the perceived product quality (Roselli, Carlucci et al 2018). Furthermore, perceived product quality has also been proved to be directly impacted by external cues (Roselli, Carlucci et al 2018) but there are very limited studies focusing on the effect of brand name (Sharma and Garg 2016), country of origin (Herz and Diamantopoulos 2017), price (Huang, Dawes et al 2017) and precautionary label on perceived product quality.…”
Section: Setting Scenario Of Pakistani Marketmentioning
confidence: 99%
“…Brand name is effective in creating product quality perceptions and it establishes the intentions of buyers towards the products (Rungtrakulchai 2018). It is also a key element for the long term success of relationships (Sharma and Garg 2016). With the brand name, buyers generally have to spend very less time to perceive the quality of the product (Randhawa, Kirca et al 2017).…”
Section: Brand Namementioning
confidence: 99%